REDESIGN WORK CHAIR WEAVER USING ERGONOMICS APPROACH IN SMALL MEDIUM ENTERPRISES OF WEAVING UKM XYZ TROSO JEPARA - Noor Nailie Azzat (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Industries of Troso weaving Jepara mostly use a handloom hand or alat tenun bukan mesin (ATBM) and their weavers use a work chair while weaving. Their working posture is so poor due to non ergonomic of work chair. It will cause fatigue and musculoskeletal disorder in years ahead as accumulation of their pain. Based on that the aim of this research is to redesign work chair for the weavers in one of Small and Medium Enterprises (UKM) XZY Troso that has 30 weavers as a respondense. The ergonomic approach use Nordic Body Map (NBM) Questionnaire to identify musculoskeletal discomfort of 30 weavers were found 3 pain in the left upper arm, 21 pain in the back, 18 pain in the waist, 9 pain in the buttock, 6 pain in the left calf and 6 in the right calf, 6 pain in the left ankle and 6 in the right ankle, 6 pain in the left foot and 6 in the right foot. To determine anthropometric dimensions of 30 weavers were measured by anthropomethry method and analyzed using statistic steps by calculating mean, standard deviation. An anthropometric calculation 5th, 50th and 95th percentiles used to specify dimensions work chair proposed. This research has generated new dimensions of work chair the seat height is 58 cm, the width is 44 cm, the depth is 35 cm, the height is 117 cm and new design of work chair has additional features like a drawer under the seat and back rest at the back.Â